Development Administration in the Developing Countries Between the Characteristics of National Bureaucracy and the Implications of International Pressures - El Bagoury, Ayman; Reyad, Doaa (The Arab Journal of Administration, 2023)
This Study examines Development Administration in the developing countries by placing national bureaucracies within a global context. The article first identifies the definition of development administration. It then explores the contexts of development administration, and the main features of national bureaucracies in the developing countries. Finally, it discusses the nature of global pressures, and their implications on development administration in the developing countries. The study reached the following results by using the ecological and analytical approaches: The growing gap between the internal characteristics of national bureaucracies in the developing countries and the requirements that need to respond to international pressures. The study indicated the following characteristics of national bureaucracy in the developing countries: The imitative pattern of bureaucracy, bureaucracy is very much concerned with Non-Productive Operators, the gap between legislature and Practice, and over-lapping in the Political and administrative Functions. The influence of the forces of global pressures on development administration varies between Western and non-Western countries, but their effects differ according to the different responses of national bureaucracies to those global challenges. The study recommends the following: Creating national models for development Administration in the developing countries resulting from their national contexts, and moving away from imported ones. Attracting qualified human resources to deal with the environment surrounding development administration in the developing countries, and qualifying the educational system to respond to these challenges.